Formas de tratamento e preservação da face em interações verbais online - Marques, Maria Aldina; Duarte, Isabel Margarida (Revista da Associação Portuguesa de Linguística, 2019)
The forms of address constitute a complex system that regulates the interpersonal relations created in the situation of communication. It is a pragmatic category with direct impact on the relations established by each social and linguistic community. As we have already mentioned in a previous unpublished communication, some forms of pronominal address, the forms Tu, Vós, Você and Vocês are a current social concern, which speakers refer to on social networks but also in more traditional public discourses, such as political discourse and media discourse or academic discourse. We aim to analyse and systematize the way in which speakers represent, in explicit comments, but also implicitly, the functions and values of these forms of address in the construction of a (im)polite speech. Within a discursive-pragmatic approach, the present analysis combines interpersonal relations and the politeness theory, in particular the pragmatic concept of face. Data for analysis were collected from web sites, namely blogs and Facebook.